Pendampingan Guru Agama Katolik Mengajar Secara Daring Pada Masa Pandemi Covid-19 - Nikolaus Anggal; Lorensius Lorensius; Stepanus Lugan; Novianus Isang (IAHN Gde Pudja Mataram, 2022)
The implementation of the government's policy on learning from home in order to prevent the spread of Covid-19 has an impact on teachers who have to face significant challenges in adapting to online learning and maintaining at least minimal communication with students, supporting student learning and development. This new adaptation in the field of education faces many obstacles, for example, the lack of teacher skills in using various learning media. This community service activity aims to provide knowledge experience and improve teacher competence in carrying out online learning by utilizing various applications that can be accessed by teachers and students to facilitate the process of teaching and learning activities. The approach used is a reflective approach by providing optimal assistance for teachers in need, especially Catholic religious teachers at primary and secondary schools in East Kutai Regency. The method of activity used is the presentation of material, practice, and performance. This mentoring activity resulted in (1) online learning modules, (2) implementation of teacher assistance in planning, implementing, and evaluating online learning, and (3) evaluation of mentoring activities. The mentoring that has been implemented has provided an increase in knowledge, understanding, and competence for teachers in implementing online learning.